The administration 3% Tamarind (Tamarindus indica) leaves ethanol extract cream inhibited the increase of tyrosinase expression and the amount of skin melanin in male Guinea pigs (Cavia porcellus) skin exposed to UV B - Angelia Ongko Prabowo; Wimpie Pangkahila; Ni Putu Sriwidyani (Neurologico Spinale Medico Chirurgico, 2021)
Background: The main factor of skin aging is exposure to sunlight, especially UV B rays. Tamarind leaves extract known containing tannins, flavonoids, and polyphenols as anti-aging agents. This study was aimed to prove the protective effect of 3% Tamarind leaves (Tamarindus indica) ethanol extract cream in inhibiting the skin aging due to exposure to UV B by evaluate the tyrosinase expression and the amount of melanin. Methods: This was a randomized post-test only control group design involving 36 subjects of male Guinea pigs, that divided into 2 groups. The control group received placebo cream and the treatment group received 3% Tamarind leaves ethanol extract cream. Cream application was given twice a day for 2 weeks. UV B were given 3 times a week for 2 weeks with a total dose of 390 mJ/cm2. Tyrosinase expression was examined by calculating the cell percentage that express the enzyme using the immunohistochemical method. The amount of melanin was examined digitally by calculating the pixel percentage of melanin in Masson Fontana staining slides. Statistical analysis by the Independent T-test to compare the mean between two groups with p=0.05 significance. Results: The mean tyrosinase expression and the mean amount of melanin in the control group was higher than treatment group. 20.650±4.911% vs 16.067±3.451%, p=0.003 and 10.461±4.916 pixel% vs 7.300±3.111 pixel%, p=0.029, respectively. Conclusion: Administration of 3% Tamarind leaves (Tamarindus indica) etanol extract cream inhibited the increase in tyrosinase expression and the amount of skin melanin in male guinea pigs (Cavia porcellus) exposed to UV B.